Analisis Penyerapan Tenaga Kerja Sektor Perhotelan dan Restoran di Kecamatan Pacet Kabupaten Mojokerto - Pradipta Sasongko; Dewie Wijayati (BISMA (Bisnis dan Manajemen), 2018)
Tourism plays an important role in Indonesia's economy both asone source of revenue for producers as well as the creator of employment and opportunities especially service business hotel accommodation and restaurant. This research using descriptive qualitative approach. The research was carried out in the District of Pacet, Mojokerto Regency. Data sources used are primary and secondary data. The technique of data collection is carried out by means of observation and in-depth interviews. While the method of data analysis using the technique of triangulation. The result showed that hotel and restaurant sector contributed to work force absorption sub-district pacet still low and not much assist in overcoming mojokerto unemployment in the county. Specifications labor at hotels and restaurants can be seen from factor is the average age 18-25 years factor high school graduate education, smk, D1 or other levels, and factor sexes prioritize women and not married.